安装中央制动器的变速器后壳改进设计与仿真 - 王源隆; 王良模; 余有平; 陈桂银; 崔保良 (Jixie chuandong)
In order to satisfy the requirement of installing central brake directly in transmission rear case,the structure of rear case is improved appropriately.The statics strength and stiffness of improved rear case are checked and the vibration performance,between original design and optimization design is compared by modal simulation analysis.According to the calculation results,the improved rear case would not suffer from the gigantic torque produced by central brake.The free modal frequencies of improved design are slightly higher than the ones of original design in corresponding modal orders,and constraints modal frequency are much higher than the excitation frequency that transmission bearing.In conclusion,this transmission rear case has good static and dynamic characteristics to meet actual request.